Pengaruh Etika Kerja Islam, Hubungan Antar Karyawan, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Komitmen Organisasi Variabel Mediasi Pada Rumah Sakit Islam Metro - Riyanto, Kuncoro Budi; Dupri, Muhammad Demsi; Safitri, Djihan (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the quality control data on the risk of product damage at PTSurya Tsabat Mandiri in reducing the risk of product damage. The type of research used isqualitative using statistical tools contained in Statistical Data Quality Control (SQC) andStatistical Process Control (SPC). The results showed that the bread production process ofPT Surya Tsabat Mandiri in January 2020 every day there were data that were notstatistically controlled and needed to be revised 1 time. This can be seen from the out ofcontrol points that occurred on the 2nd, 5th, 7th, 9th, and 25th days. Then corrective actionis taken by looking for the causes of defects so that the points that are out of control arewithin the control limits of UCL and LCL (in of control) so that the production process canbe said to be statistically controlled.